Language development of bilingual children; The acquisition of tense and aspect in an Italian-Indonesian child: A case study - Soriente, Antonia (UI Scholars Hub, 2014)
This paper describes the development of temporal expressions in a bilingual child acquiring two typologically distinct languages: Italian and Indonesian. These languages differ from one another in the way tense and aspect are encoded and it is interesting to observe what kind of cross-linguistic influence one language system has on the other. Italian verbs are heavily inflected for person, number as well as for tense, aspect and mood, whereas, in Indonesian, the encoding of tense and aspect is lexical rather than morphological; moreover encoding is optional when the context is sufficiently clear. This means that tense and aspect in Indonesian is often marked pragmatically rather than grammatically. This paper considers the interference effects that result from simultaneously acquiring these two typologically distinct systems.